THE INFLUENCE OF CULTURAL IDENTITIES IN SECOND LANGUAGE ACQUISITION: A PERSPECTIVE FROM SECONDARY PROGRAM (SEMARANG MULTINATIONAL SCHOOL) - Ali, Ali Mohamed; Mujiyanto, Yan (English Education Journal, 2017)
Any student goes to the classroom with his/her own cultural identity. In other words, Every student comes to the classroom with a set of characteristics and behaviors that make him or her unique and that will affect his or her academic achievements in the future. The purpose of this study is to investigate the influences of cultural identities in second language acquisition (a perspective from secondary school) at SEMARANG MULTINATIONAL SCHOOL, Indonesia. Which known as an International Institution that presented International educational standers. This article covers a descriptive qualitative approach which used different methods to collect the data, they were (focus groups discussion for six students and conducting interviews with three of their teachers). The findings of this study revealed three main results. Firstly, there were several steps to enhance the second language learners and still there are some factors that affect Indonesian students entirely adaption for English as a second language which are: the fluency constraints and the fear that they still not qualified when it comes to communicate by using modern English language, also the grammar structure while doing common conversations. Secondly, the findings obviously showed the positive influence of cultural identities on the process of second language acquisition and students' academic achievements in the future. Thirdly, it was briefly revealed that to adapt English as a second language it is needed to exceed the negative intrinsic and extrinsic factors while taking place the positive factors, in general the negative factors which arose in the results somehow mislead them to achieve the completely adaption. Some pedagogical suggestions from the writer were recommended to students, teachers and institutions: For students to be more brave, open-minded and outgoing (no shyness in education). The necessity of teachers' conversant for culture diverse during learning context and finally, The Ministry of Indonesian Education has the choice to improve English language interest by involving it in all schools not only the International, but also in national institutions to be language of education.